Implementasi CITES Oleh Indonesia Dalam Perdagangan Hiu Martil dan Hiu Sutra - Carina Maynelfa; Anita Afriani Sinulingga; Silvi Cory (Andalas Institute of International Studies, 2023)
Analyzing the obstacles faced by Indonesia when implementing Convention on International Trade in Endangered Species of Wild Flora and Fauna(CITES) rules regarding the protection of sharks that are listed in Appendix II. Hammerhead sharks and silk sharks are the types of sharks that were listed in Appendix II in 2013 and 2016. Indonesia has ratified CITES from 1978 until now it is still implementing CITES rules. Various regulations have been made by the government to show its seriousness in dealing with the problem of catching sharks for trade. There has been an increase in shark catches and trade despite various efforts. The obstacles experienced by Indonesia were analyzed using the concept of Abram Charles and Chayes, namely regime compliance which has three indicators, namely ambiguity, lack of capacity, and temporal dimension. This study uses a descriptive methodology with a qualitative approach. The researcher found that Indonesia experienced obstacles in implementing the CITES regime for the protection of sharks, especially hammerheads and silks because of the national rules derived from the ratified CITES convention causing doubts or ambiguity in domestic regulations and Indonesia's limited capacity at the level of education and technology for coastal communities as well and also fishermen's dependence on haul from sharks. Several conditions experienced by Indonesia are obstacles in implementing CITES rules, especially the protection of hammerhead sharks and silk sharks.